How to develop critical-reflective thinking in our learning from questions to think? - Gómez Navarro, María Victoria
This article, through document management, intends to invite reflection on the way in which the formation of critical-reflective thinking is developed in apprentices, through guided questions to encourage positions that question the quality of their training, of the In the same way, the need to encourage the use of real problem situations is identified, generating discussion to promote the practice of reflexive and purposeful questioning by all the actors in the training process. In the bibliographic search process, theoretical experts were found who offer interesting concepts and practices to bring this proposal to a successful conclusion